Higher levels of D2R and D3R in the frontal–striatal regions are associated with reduced perseverative reward seeking after opioid abstinence - Yingying Li; Yingying Li; Xigeng Zheng; Xigeng Zheng; Cong Gao; Cong Gao; Shao Li; Zhengkui Liu; Zhengkui Liu; Meixuan Lv; Meixuan Lv; Fei Xiao; et al. (Frontiers in Behavioral Neuroscience)
IntroductionThe lower levels of dopamine D2 receptor (D2R) in the striatum and the heightened levels of dopamine D2 receptor (D3R) in the midbrain have been linked to impulsive behavior and risky decision-making associated with drug dependence. While D3R has been considered a potential target for treating drug dependence, the connection between D3R in the prefrontal-striatal regions and maladaptive drug-related behaviors remains poorly understood.MethodsThis study utilized two high-cost tasks to investigate perseverative reward seeking, specifically conflict-based approaching behavior and persistent responding behavior under a progesterone receptor (PR) procedure. Additionally, D2R and D3R levels in the medial prefrontal cortex (mPFC) and striatum were examined through Western blotting.ResultsAfter each task, male rats were divided into two subpopulations: high-approaching vs. low-approaching and high-responding vs. low-responding. Rats treated with morphine (MOR) exhibited a 3 fold increase in the likelihood of developing high-approaching or high-responding behaviors compared to drug-naïve rats. D2R expression was higher in the ventral striatum of morphine-treated, low-approaching rats than high-approaching rats, negatively correlating with approaching behaviors within the morphine-exposed group. After six consecutive PR sessions, D3R levels in the dorsal striatum differed significantly between morphine-treated, low-responding rats and morphine-treated, high-responding rats, negatively correlating with responding behaviors within the morphine-exposed group. An intriguing finding was the non-linear relationships, resembling an inverted U shape, observed between the level of D3R in the mPFC and reward-seeking behaviors, as revealed by both tasks.DiscussionThe elevated or relatively higher levels of D2R and D3R in the frontal-striatal regions may serve as protective factors for individuals abstaining from opioids, enabling them to control their reward-seeking behavior better.